So What Do You Do? Experimenting with Space for Social Creativity - Ariane Berthoin Antal; Victor J. Friedman (Knowledge and Action, 2017)
This chapter investigates the relationship between physical space and processes of creative thinking and action. The authors build on organizational and sociological literature about social space and aesthetics, then illustrate how the latter two aspects influenced each other in five action experiments. Small mixed groups explored how they would use a studio to facilitate social innovation and to strengthen the link between the Max Stern Jezreel Valley College in Israel and the surrounding communities. Analysis of the video recordings identified seven configurations of social space that changed over time as the participants engaged in the task. The authors suggest that the undifferentiated and unencrusted nature of the space was both a source of uncertainty and potential for the participants. Some groups generated more innovative processes and products than others. The study also offers insights into the importance of embodied action and verbal discourse in innovative processes.
Keywords: 330; Social space; Aesthetics; Social innovation; Undifferentiated space; Unencrusted space; Embodied knowing